(untitled) (Proceedings of Voronezh State University. Series: Geology, 2022)
Introduction: The structural segmentation and geological and geophysical characteristics of the rift zone of the southern segment of the Mid-Atlantic Ridge (MAR) between the Agulhas-Falkland fracture zone and the Bouvet Triple Junction are considered. Methodology: The main research method was the physical modeling of the segmentation of the axial zone of the southern segment of the Mid-Atlantic Ridge. The simulation was carried out in the Laboratory of Experimental Geodynamics of the Museum of Earth Science, Lomonosov Moscow State University. Results and discussion: It was shown that the axial morphology of the rift zone changes from north to south from a slow spreading rift valley morphology to an axial uplift morphology typical for fast spreading ridges. At the same time, the nature of the morphostructural segmentation of the rift zone also changes: transform faults typical of the northern part of the segment are replaced by non-transform axial displacements in the south. Structural changes are also reflected in the characteristics of anomalous potential fields. Mathematical and physical modeling were compared. Physical modeling is now relatively rarely used for the investigation of the dynamics of the lithosphere-mantle system. Conclusions: Experimental studies carried out using physical modeling of structure -forming deformations, performed using a unique installation, showed that changes in the morphostructural segmentation of the rift zone of the MAR are associated with a change in the rheological properties of the lithosphere (decrease in the thickness of the brittle layer of the lithosphere) caused by increased heating of the mantle as it approaches Bouvet and Shon hot spots, located near the southern end of the MAR segment.